A SYSTEMATIC REVIEW OF GRAMMAR GAMES FOR ENGLISH LANGUAGE TEACHING (ELT) - Roja Arribath Eka Daep; Amalia Farid; Nafan Tarihoran (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Grammar games have become widely adopted in English Language Teaching (ELT) to enhance students' grammatical competence through engaging and interactive approaches. This study systematically reviews existing literature on the effectiveness of grammar games by analyzing their application, benefits, and overall impact. Using the Systematic Literature Review (SLR) method, data were collected from Taylor & Francis, PubMed, and Mendeley databases. From an initial pool of 102 articles, 14 met the eligibility criteria, with nine included in the final analysis through the PRISMA framework. The findings demonstrate that grammar games significantly enhance student motivation, participation, and mastery of grammar. Tools like Kahoot!, Duolingo, Quizizz, and traditional games contribute to a more student-centered environment. Challenges such as time constraints and off-focus behavior were noted. The study recommends further research into long-term effects and the integration of grammar games into complex grammar instruction.